A Case of Visceral Leishmaniasis in a 4-Year-Old Child Living in Nonendemic Area Located in Suburbs of Dakar, Senegal - Magatte Ndiaye; Dienaba Fafa Cissé; Aicha Djigal; Aminata Sow; Souléye Lélo; Fatoumata Ly; Isaac A. Manga; Mame Ami Diouf; Doudou Sow; Oumar Gaye; Boubacar Camara; Babacar Faye (Case Reports in Infectious Diseases)
Visceral leishmaniasis (VL) is an infectious disease caused by protozoa of the genus Leishmania. Sporadic cases are observed in nonendemic areas and often associated with limited foci; therefore, the disease is easily overlooked. In addition, other diseases have similar clinical symptoms, which make it difficult for clinicians to make an accurate diagnosis and to provide effective treatment. We identified visceral leishmaniasis in a 4-year-old child in Pikine, Senegal. The patient was admitted to the Pikine National Teaching Hospital for haemorrhagic, tumoral, and infectious syndromes. At admission, the patient presented with epistaxis and gingivorrhagia, a severe anaemic syndrome poorly tolerated, a systemic inflammatory response syndrome with fever at 39.5°C, a tumoral syndrome with 11 cm of hepatomegaly and 12 cm of type IV splenomegaly, and noninflammatory macropoly adenopathies. A spinal cord puncture was performed, and direct microscopy examination of the sample after GIEMSA staining revealed amastigote forms of Leishmania. The PCR amplification of extracted DNA from the bone marrow aspiration using specific primers for VL (forward and reverse) confirmed that VL was responsible for the infection. A treatment with meglumine antimoniate (Glucantime) was given and it gave a successful outcome with remission of clinical symptoms and favourable evolution with 3 months hindsight. Conclusion. This visceral leishmaniasis case diagnosis in Senegal has shown that, apart from haematological malignancies, this disease must be considered in combination with a tumor syndrome, haemorrhagic syndrome, and infectious syndrome.